Metabolic signature genes associated with susceptibility to pyruvate kinase, muscle type 2 gene ablation in cancer cells - Jung, Yuri; Jang, Ye Jin; Kang, Min Ho; Park, Young Soo; Oh, Su Jin; Lee, Dong Chul; Xie, Zhi; Yoo, Hyang-Sook; Park, Kyung Chan; Yeom, Young Il (Molecules and cells, 2013)
Pyruvate kinase, muscle type 2 (PKM2), is a key factor in the aerobic glycolysis of cancer cells. In our experiments, liver cancer cell lines exhibited a range of sensitivity to PKM2 knockdown-mediated growth inhibition. We speculated that this differential sensitivity is attributable to the variable dependency on glycolysis for the growth of different cell lines. Transcriptome data revealed overexpression of a glucose transporter (GLUT3) and a lactate transporter (MCT4) genes in PKM2 knockdown-sensitive cells. PKM2 knockdown-resistant cells expressed high levels of the lactate dehydrogenase B (LDHB) and glycine decarboxylase (GLDC) genes. Concordant with the gene expression results, PKM2 knockdown-sensitive cells generated high levels of lactate. In addition, ATP production was significantly reduced in the PKM2 knockdown-sensitive cells treated with a glucose analog, indicative of dependency of their cellular energetics on lactate-producing glycolysis. The PKM2 knockdown-resistant cells were further subdivided into less glycolytic and more (glycolysis branch pathway-dependent) glycolytic groups. Our findings collectively support the utility of PKM2 as a therapeutic target for high lactate-producing glycolytic hepatocellular carcinoma (HCC).